Expansion of the genotypic and phenotypic spectrum in patients with KRAS germline mutations. Issue 2 (20th October 2006) - Zenker, Martin; Lehmann, Katarina; Schulz, Anna Leana; Barth, Helmut; Hansmann, Dagmar; Koenig, Rainer; Korinthenberg, Rudolf; Kreiss-Nachtsheim, Martina; Meinecke, Peter; Morlot, Susanne; Mundlos, Stefan; Quante, Anne S; et al.
Abstract : Background: Noonan syndrome, cardio-facio-cutaneous syndrome (CFC) and Costello syndrome constitute a group of developmental disorders with an overlapping pattern of congenital anomalies. Each of these conditions can be caused by germline mutations in key components of the highly conserved Ras-MAPK pathway, possibly reflecting a similar pathogenesis underlying the three disorders. Germline mutations in KRAS have recently been identified in a small number of patients with Noonan syndrome and CFC. Methods and results: 260 patients were screened for KRAS mutations by direct sequencing. Overall, we detected KRAS mutations in 12 patients, including three known and eight novel sequence alterations. All mutations are predicted to cause single amino acid substitutions. Remarkably, our cohort of individuals with KRAS mutations showed a high clinical variability, ranging from Noonan syndrome to CFC, and also included two patients who met the clinical criteria of Costello syndrome. Conclusion: Our findings reinforce the picture of a clustered distribution of disease associated KRAS germline alterations. We further defined the phenotypic spectrum associated with KRAS missense mutations and provided the first evidence of clinical differences in patients with KRAS mutations compared with Noonan syndrome affected individuals with heterozygous PTPN11 mutations and CFC patients carrying a BRAF, MEK1 or MEK1 alteration, respectively. We speculate that the observed phenotypic variability may be related, at least in part, to specific genotypes and possibly reflects the central role of K-Ras in a number of different signalling pathways.